Skin Paddles Improve Muscle Flap Salvage Rates After Microvascular Compromise in Lower Extremity Reconstruction. Issue 1 (July 2018) - Stranix, John T.; Jacoby, Adam; Lee, Z-Hye; Anzai, Lavinia; Saadeh, Pierre B.; Thanik, Vishal; Levine, Jamie P.
Abstract : Purpose: Free tissue transfer after lower extremity trauma is associated with notoriously high complication rates. Theoretically, the inclusion of a cutaneous paddle on muscle free flaps may improve clinical flap monitoring. The effect of skin paddle presence on muscle free flap salvage outcomes after take-back was examined. Methods: Retrospective query of our institutional free-flap registry (1979–2016) identified 362 muscle-based flaps performed for soft tissue coverage after below-knee trauma. Primary outcome measures were perioperative complications, specifically take-back indications, timing, and flap salvage rates. Univariate and multivariate regression analyses were performed where appropriate. Results: The most common flaps were latissimus dorsi (166; 45.9%), rectus abdominis (123; 34%), and gracilis (42; 11.6%) with 90 flaps (24.9%) including skin paddles. Take-backs for vascular compromise occurred in 44 flaps (12.2%), of which 39% contained a skin paddle while 61% did not. Overall salvage rate was 20.5%, with 31.8% partial failures and 47.7% total flap losses. Muscle flaps with skin paddles were more likely to return to the operating room within 48 hours postoperatively than those without (57.1% vs 18.2%, P = 0.036). After take-back, significantly more muscle flaps with skin paddles were salvaged compared with muscle flaps without paddles (35.7% vs 4.5%, P = 0.024). Similarly, more muscle-only flaps after take-back failed compared with their counterparts with skin paddles (95.5% vs 65.3%, P = 0.024). Conclusions: Muscle flaps with a cutaneous paddle were associated with earlier return to the operating room and more successful flap salvage after take-back compared with muscle-only flaps. These findings suggest that skin paddle presence may improve clinical flap monitoring and promote recognition and treatment of microvascular compromise in lower extremity reconstruction.